Exercise and spirulina control non-alcoholic hepatic steatosis and lipid profile in diabetic Wistar rats - Moura, Leandro P. [UNESP]; Puga, Guilherme M. [UNESP]; Beck, Wladimir R. [UNESP]; Teixeira, Inaian P. [UNESP]; Ghezzi, Ana Carolina [UNESP]; Silva, Glaucio A. [UNESP]; Mello, Maria Alice R. [UNESP] (Biomed Central Ltd., 2011)
Background: Diabetes mellitus is associated with metabolic dysfunctions, including alterations in circulating lipid levels and fat tissue accumulation, which causes, among other pathologies, non-alcoholic fatty liver disease (NAFLD).Aim of the study: The objective of this study was to analyse the effects of physical exercise and spirulina intake on the control of NAFLD in diabetic Wistar rats.Methods: Diabetes was induced in the animals through intravenous administration of alloxan. The rats were divided into four groups: Diabetic Control (DC) - diabetic rats fed with a control diet and no physical exercise; Diabetic Spirulina (DS) - diabetic rats fed with a diet that included spirulina; Diabetic Spirulina and Exercise (DSE) - diabetic rats fed with a diet that included Spirulina and that exercised; and Diabetic Exercise (DE) - diabetic rats fed with a control diet and that exercised.Results: The groups DS, DSE, and DE presented lower plasma concentrations of LDL cholesterol than DC, as well as lower levels of total liver lipids in groups DS, DSE, and DE in comparison to DC.Conclusion: Thus, spirulina appears to be effective in reducing total circulating levels of LDL-cholesterol and hepatic lipids, alone or in conjunction with physical exercise in diabetic rats.